Characteristics and heavy metal leaching of ash generated from incineration of automobile shredder residue - Lee, Hwa Young (ELSEVIER, 2007)
Bottom and fly ash collected from automobile shredder residue (ASR) incinerator have been characterized in terms of particle size, compositions, and heavy metal leaching by the standard TCLP method. Two alternative methods were also examined for the treatment of heavy metals in ASR incinerator ash from the aspect of recycling into construction or lightweight aggregate material. It was remarkable that the concentration of Cu was very high compared to common MSWI bottom and fly ash, which was probably originated from copper wires contained in ASR. As a whole, the results of characterization of ASR fly ash were in good agreement with common MSWI fly ash in terms of particle size, pH, and water-soluble compounds. It was clearly found that heavy metals could be removed thoroughly or partly from ASR fly ash through acid washing with dilute HCl solution so that the remaining fly ash could be landfilled or used as construction material. It was also found that the amount of heavy metal leachability of lightweight aggregate pellet prepared with ASR incineration ash could be significantly decreased so that the application of it to lightweight aggregate would be possible without pre-treatment for the removal of heavy metals. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: WASTE INCINERATION; FLY-ASH